Substitutes for Bear Bile for the Treatment of Liver Diseases: Research Progress and Future Perspective. (21st March 2016) - Li, Sha; Tan, Hor Yue; Wang, Ning; Hong, Ming; Li, Lei; Cheung, Fan; Feng, Yibin
Abstract : Bear bile has been a well-known Chinese medicine for thousands of years. Because of the endangered species protection, the concept on substitutes for bear bile was proposed decades ago. Based on their chemical composition and pharmacologic actions, artificial bear bile, bile from other animals, synthetic compounds, and medicinal plants may be the promising candidates to replace bear bile for the similar therapeutic purpose. Accumulating research evidence has indicated that these potential substitutes for bear bile have displayed the same therapeutic effects as bear bile. However, stopping the use of bear bile is a challenging task. In this review, we extensively searched PubMed and CNKI for literatures, focusing on comparative studies between bear bile and its substitutes for the treatment of liver diseases. Recent research progress in potential substitutes for bear bile in the last decade is summarized, and a strategy for the use of substitutes for bear bile is discussed carefully.